Agent assisted interactive algorithm for computationally demanding multiobjective optimization problems. (9th June 2015) - Ojalehto, Vesa; Podkopaev, Dmitry; Miettinen, Kaisa
Abstract : Highlights: Assist a decision maker when solving multiobjective optimization problem. Replace computationally expensive problem with an inexpensive surrogate problem. Surrogate constructed based on the preferences of the decision maker. Applied for solving a two-stage separation problem. Abstract: We generalize the applicability of interactive methods for solving computationally demanding, that is, time-consuming, multiobjective optimization problems. For this purpose we propose a new agent assisted interactive algorithm. It employs a computationally inexpensive surrogate problem and four different agents that intelligently update the surrogate based on the preferences specified by a decision maker. In this way, we decrease the waiting times imposed on the decision maker during the interactive solution process and at the same time decrease the amount of preference information expected from the decision maker. The agent assisted algorithm is not specific to any interactive method or surrogate problem. As an example we implement our algorithm for the interactive NIMBUS method and the PAINT method for constructing the surrogate. This implementation was applied to support a real decision maker in solving a two-stage separation problem.